Labour market flows and worker trajectories in Canada during COVID-19 - Pierre Brochu; Jonathan Créchet; Zechuan Deng (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
Labour Market Flows and Worker Trajectories in Canada during COVID-1We use the confidential-use files of the Labour Force Survey (LFS) to study the employment dynamics in Canada from the beginning of the COVID-19 pandemic through to mid-summer. Using the longitudinal dimension of this dataset, we measure the size of worker reallocation, and document the presence of high labour market churning, that persists even after the easing of social-distancing restrictions. As of July, many of the recent job losers - especially those who had been temporarily laid-off between February and April - have regained employment. However, this apparent strong recovery dynamics hides important heterogeneity, and large groups of workers, such as those who were not employed prior to the pandemic, face important difficulties with finding a job. Three factors appear to be key in accounting for the incomplete employment recovery of July: (1) the unusually high separation flows that characterize the labour market in the reopening phase; (2) the low reemployment probability of recent job losers who were classified as out of the labour force during the lockdown; and (3), the low job-finding rate of individuals who were out of work prior to the pandemic. Our results further suggest that gross job losses were higher among women and young workers during the shutdown, and that older workers were more likely to leave the labour force when the economy reopened.
Keywords: 330; Arbeitsmarkt; Arbeitsmobilität; Epidemie; Coronavirus; Kanada